İstanbul-Silivri-Kavaklı havzası ve dolayının hidrojeolojik incelenmesi - Çopuroğlu, Muhterem (Fen Bilimleri Enstitüsü, 1997)
Silivri-Kavaklı-Ortaköyü içine alacak şekilde yaklaşık 45 km2'lik yüzölçümü bulunan Kavaklı,aşağı ve kömürlük dereleri drenaj alanında yapılan bu çalışma, Kavaklı havzasının yeraltısuyu bilançosunu ve sorunlarını ortaya koymak için yapılmıştır. Sonuç olarak, hazılanan bu rapor "Yüksek Lisans Tezi" olarak Uygulamalı Jeoloji Anabilim Dalı'na sunulmuştur. İnceleme alanı Marmara Bölgesinin Trakya kesiminde İstanbula 70 km uzaklıktaki Silivri ilçesinin doğusunda yeralır. Bu bölge 41°03'30" ile 41°07'30"kuzey enlemleri ve 28° 18' 35" ile 28° 23' 30" doğu boylanılan arasındadır. Genel olarak orta kuşak deniz iklimi karakteri taşır. Kışlar ılık ve yağışlı, yazlar sıcak ve kurak geçer. Florya gözlem istasyonu verilerine göre yıllık toplam yağış yüksekliği 642,4 mm. dir. En yüksek kot 236 metre ile Kum tepedir, akarsu ağını Ortaköy'ün kuzeyinden beslenen Aşağı dere ile Kavaklı köyünün kuzeyinden beslenen Kömürlük dere ve kavaklı dere şekillendirir. Ancak bu dereler kuru deredir. Kışın yağışın fazla olduğu aylarda yüzeysel akış olabilmektedir. Hazırlanan Su bilançosunda, toplam yıllık yağış 642,4 mm, gerçek buharlaşmanın 428,5 mm. ve akışın 213,9 mm. olduğu görülmektedir. Buna göre inceleme alanında toplam yıllık yağışın 428,5 mm.'si yani %67'si buharlaşma-terleme yolu ile atmosfere geri dönmekte, geriye kalan 213,9 mm ise yeraltı ve yerüstü suyu olarak akışa geçmektedir. Bu miktar tüm yağışın %33' üdür. İnceleme alanını hemen hemen tümüyle kaplayan Oligosen tortulları, iyi tabakalanmış kumlu marnlar ve kumtaşı, kiltaşı, sihtaşı ardalanmasından oluşur. Kıyışa! ve sığ denizel fasiyeste gelişen akarsu ve lagün ortamlara ait bu karakteristik kayaç birimleri ortam koşullarına uygun olarak birbirleriyle karmaşık ilişkiler içinde bulunur. Kuvaterner çökeller dere yataklarında alüvyonel birikimler şeklindedir. Sözkonusu formasyon bütün olarak yan geçirimli taneli ortamı oluşturur. Gevşek çimentolu kum, kil ve sütten oluşan bu birim içinde açılan kuyuların debisi 0,3 it/sn ile 18 it/sn arasında değişmektedir. Transmissibilite 3-17 nr/gün/m değerleri arasındadır. Yeraltısuyu, özellikle kumlu ve çakıllı düzeylerden alınmaktadır. Kumtaşları merceksellik gösterir. Akiferin beslenmesi yağıştan sızma ve sulamadan süzülmelerle olmaktadır. Boşalım ise buharlaşma - terleme ve suni çekim ile olmaktadır. Beslenimin % 80'i olan 2.000.000 mVyıl yeraltısuyu emniyetli verimi olarak kabul edilmiştir. İnceleme alanı içinde açılan sondaj kuyulanndan alınan su örneklerinin tümü T.S 266'ya göre içilebilir özelliktedir. Wilcox diyagramına göre çalışma alanımızdaki sular çok iyi, iyi kullanılabilir sular niteliğindedir. Sulama suyu olarak C3Sj ve C^ sınıfında olduğu görülmüştür. Dolayısıyla suların, toprakta alkali tehlikesinin düşük, tuzluluk tehlikesinin orta ve yüksek olduğu belirlenmiştir. Suların Piper diyagramında sergiledikleri kimyasal bileşim havzanın litolojik özellikleri ile uyum göstermiştir. Hakim litoloji kumtaşı, kiltaşı ve marndır. Kumtaşlannın kuzeyden çatalca masifi yönünden taşınıp gelen kireçtaşı gereçleriyle geliştiği anlaşılmaktadır.

This study covering approximately 45 km2 of land laying among Aşağı, Kömürlük and Kavaklı streams, basically a drainage area including Silivri-Kavaklı-Ortaköy towns of Trace has been made in order to expound ground water reserves of the Kavakh basin as well as to develop remedies for related problems arising therefrom; and it has been submitted as "Masters Thesis" to the Department of Geology, Applied Sciences for perusal and convenience. The basic goal of this study is providing sufficient and adequate solutions to such problems which arise in case water requirement of the region is met solely from ground water resources, and specifying the ground water potential of the region. Land research, in situ has given a lot of insight to the author, and ali relevant data by previous studies carried out in the region have been taken into consideration, and as a result, hydrogeological properties of the region have been indicated. Further, pump test results have been analyzed to specify the ground water potential of the region. A special emphasis has been made in order to specify the dynamic reserve considering devastating consequences that may come through in the future due to excess usage of ground water by means of unpermitted drilling wells. in addition, water quality has been examined for tap-water, irrigation and drinking purposes. Researched area lays in the East of Silivri province, some 70 km.s. from istanbul city centre in trace. This area lays between 41° 03' 30" - 41° 07'30" Northern latitude and 28°18'35"-28°23'30" Eastern longitude. Moderate maditerranean climate prevails in the region. Modarately cool and rainy winter as against a relatively höt and dry summer season mark their characteristics respectfully. As per the data issued by Florya Observation Station, annual rainfall works out to 642,4 mm. at an avarage. The crest of the region is Kumtepe (236m.). Aşağıdere generating from the North of Ortaköy, Kömürlükdere and Kavaklıdere generating from the North of Kavakh are the basic streams. However they are of insignificant importance since they remain dry most of the times. Only in the vvinter season, some surface flow takes place due to heavy rain. Balancesheet of water supply gives an average annual rain of 642.4 mm., evaporation 428.5mm. and flow 213,9 mm.in the region. Based upon these findings, 428,5 mm. total annual rain which marks 67% recycles onto atmosphere through evapo-transpiration and only 213,9 mm which constitutes 33% flows either as surface water ör ground water. Some six operative wells suitable for reliable pump test practices have been examined Transmissibility coefficients for present aquifer have been calculated by using reliable output from those wells. in addition, monthly water level measurements for the wells no. 129, 131, 112 and 68 by State Hydraulic Works Agency between August 1994-November 1996 have been taken into consideration. vii Montly ground water measurements as well as time-graphics are provided herewith in correlation with Florya Observation Station statistics as regards rainfall. in jully, August and September, groundwater level remains the lowest vis a vis April and May, the highest. Due to population movements and growth in the region during the summer season, excess withdrawal results in drastic recession of ground water level. Grafics reflecting variations in the ground water level in comparasion to monthly rainfall figures evidence that rainfall infiltrate into groundwater in a period of öne month(Fig.l) l «.,.*. |w«-|,,,,,7, ı ı ı ı I ı |j ı iTl l l l l l l l l l T l l l l l II Table ^ A \K \ /\ \l \ / \. \ / \ \ / \ f W K. 12CC, Tl.n. f 11 "M r" '.' -. F^ Rainfall ; t ı «'.o _ "J-, -: . : K-. o «o -,.-.-İ:. - f-ı .].. " :- > n :\.'.. r'-- ..; - ~r-> *"' '^U'< ] 4-T" ti Fİ n '>- "::^ &<% »..\Trlh: ^îy> P? ^ -vf^ ^l~ l cJiltt;MU'^1fNMCT-^^-i-y^ w& Fiği. Variations Rainfall and Goundwater Table Oligocene sediments of the researched area contain good laminated sandy marl, sandstone, siltstone and claystone which are formed in a sequential order. Such rock units embody characteristic properties of coastal and shallow marine facies oriented running water and lagoon environments and they are in complex relations with each other. Quarterner depositions are found in alluvional accumulations in stream beds. Wells drilled into such units which are composed of unconsolidated cement contained sand, clay and şilt, yield an output between 0,3 It/sec and 18 It/sec. Transmissibility ranges between 3-17 m3/day/m. Groundwater is exploited from sandy and gravely layers sandstones are of pearched aquifer properties which is a positive characteristic as to reserving groundwater inlarge scales; but nevertheless it turns out to be a negative characteristic since it gives way to a recharge confined to a smaller area. viii Random samples obtained from wells within the researched area have been examined as to potable water and irrigation water utilization purposes. Wilcox, Riverside and Schoeller diagrams are thus provided herein as to potable water. in addition, Piper and Schoeller semilogaritmic diagrams are both used in order to specify the litology dominant in the formation of chemical compositions, and to classify water samples as to their chemical compositions(Fig.2). Gibbs diagram provided herein indicates the eflfect of lithology in such compositions.
Hydrogeological investigation of Kavaklı (İstanbul-Silivri) basin and vicinity
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Hidrojeoloji; Kavaklı havzası; Hydrogeology; Kavaklı basin